2016
DOI: 10.1002/hed.24583
|View full text |Cite
|
Sign up to set email alerts
|

Artificial nutrition dependence after cetuximab versus cisplatin combined with radiotherapy for advanced head and neck cancer: A propensity score–matched analysis

Abstract: Background. The purpose of this study was to compare the effect of cetuximab-based radiotherapy (RT) with cisplatin-based concomitant chemoradiotherapy (CCRT) on artificial nutrition dependence in locoregional advanced head and neck cancer. Methods. We identified patients treated with cetuximab-based RT or CCRT between 2012 and 2014 in a Japanese national database, and used propensity score-matched analyses to evaluate artificial nutrition dependence for 30 days after starting chemotherapy and at hospital disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Many of the patients in both study groups needed an enteral feeding tube; however, throughout the study, there were significantly more patients in total who received an enteral feeding tube in the cisplatin group. This is in accordance with findings by Ishimaru et al 40 However, this is in contrast to some other studies that found the need for nutritional support with enteral feeding tubes to be equal or even higher for patients treated with cetuximab 41,42 . Since the negative side effects from the treatment continue even after the treatment has ended, it might be possible that the support the cisplatin‐treated patients had from the enteral feeding tube earlier during the treatment helped to slow further reductions in weight.…”
Section: Discussionsupporting
confidence: 94%
“…Many of the patients in both study groups needed an enteral feeding tube; however, throughout the study, there were significantly more patients in total who received an enteral feeding tube in the cisplatin group. This is in accordance with findings by Ishimaru et al 40 However, this is in contrast to some other studies that found the need for nutritional support with enteral feeding tubes to be equal or even higher for patients treated with cetuximab 41,42 . Since the negative side effects from the treatment continue even after the treatment has ended, it might be possible that the support the cisplatin‐treated patients had from the enteral feeding tube earlier during the treatment helped to slow further reductions in weight.…”
Section: Discussionsupporting
confidence: 94%
“…A standardized difference of >10% was defined as out of balance." [31] Estimation of Propensity Score Specifications regarding the type of regression model used to generate propensity scores. ".…”
Section: Methodsmentioning
confidence: 99%
“…Since then the studies have had mixed results with: one showing no difference in weight loss or feeding tube use (Ye, Hay, Laskin, Wu, & Ho, 2013); one showing higher rate of tube placement with Cisplatin (Levy et al, 2014); one showing higher need for nutrition support with Cetuximab (Magrini et al, 2015); and a small case series of patients receiving Cetuximab with a high use of feeding tubes (11/14 patients) and high rates of mucositis (Yokota et al, 2015). The most recent study (n=500) found use of nutrition support was higher in the Cisplatin group at 30 days post commencement of treatment, but no different on completion of treatment (Ishimaru et al, 2016).…”
Section: Impact On Quality Of Lifementioning
confidence: 96%